2021
DOI: 10.3390/ijerph18157763
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Lifestyle Behavior Clusters to Dyslipidemia in China: A Compositional Data Analysis

Abstract: Dyslipidemia is associated with lifestyle behaviors, while several lifestyle behaviors exist collectively among some populaitons. This study aims to identify lifestyle behavior clusters and their relations to dyslipidemia. This cross-sectional study was conducted in Wuhai City, China. Cluster analysis combined with compositional data analysis was conducted, with 24-h time-use on daily activities and dietary patterns as input variables. Multiple logistic regression was conducted to compare dyslipidemia among cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…In this study, we found that unhealthy sleep quality was more prevalent among participants of low SES, which was consistent with the previous study ( 50 ). Although we constructed a lifestyle score, including baseline sleep quality in the sensitivity analysis, the results remained similar, suggesting that other unmeasured lifestyles may play a role, such as sedentary behavior ( 17 , 51 ). Existing study shows SES-related health effects of social environments (e.g., isolation and the lack of engagement in social networks) may be even more important than those of physical environments ( 8 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, we found that unhealthy sleep quality was more prevalent among participants of low SES, which was consistent with the previous study ( 50 ). Although we constructed a lifestyle score, including baseline sleep quality in the sensitivity analysis, the results remained similar, suggesting that other unmeasured lifestyles may play a role, such as sedentary behavior ( 17 , 51 ). Existing study shows SES-related health effects of social environments (e.g., isolation and the lack of engagement in social networks) may be even more important than those of physical environments ( 8 ).…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, lifestyles are mutually connected and limited studies conducted lifestyle score to evaluate its effect on the socioeconomic inequities in dyslipidemia. Based on the literature, both SES (low SES) ( 16 , 17 ) and unhealthy lifestyles (e.g., less physical activity, irrational diet, etc.) ( 18 , 19 ) are associated with the risk of dyslipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study of 7,586 adults found that heavy smokers had signi cantly lower HDL-C and TC levels than light smokers after quitting smoking [22]. Sedentary behaviors and general and central obesity have also been reported to have a positive relationship with dyslipidemia in various studies [7,8,23].…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al's study in North China shows that dyslipidemia is negatively correlated with HLS [13]. In a study based on cluster analysis, a higher prevalence of dyslipidemia was reported in a cluster whose population had long-term sedentary behavior, the shortest sleep, and a high salt and oil diet [7]. A study on the Iranian population has shown that the use of statins for dyslipidemia patients is low, and 44.2% of patients who are aware of their dyslipidemia receive statin treatment [14].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation